2014
DOI: 10.3103/s1068367414050103
|View full text |Cite
|
Sign up to set email alerts
|

Genetic similarity and differences between the Orobanche cumana Wallr. Populations from Russia, Kazakhstan, and Romania revealed using the markers of simple sequence repeat

Abstract: The molecular genetic diversity of the broomrape (O. cumana) populations, parasitizing on sun flower in Russia, Romania and Kazakhstan, was studied with codominant microsatellite markers. By means of cluster analysis, the populations of broomrape were divided into two clusters, regardless of their racial com position. In the first cluster, 19 samples from Russia and Kazakhstan, representing one gene pool are grouped; the second cluster consisted of five populations from Romania, united in another pool. Accordi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 9 publications
1
12
0
Order By: Relevance
“…Pineda-Martos et al (2013) detected 19 alleles (2 to 3 alleles/locus) for the same SSR loci as in our study. In the work of Guchetl et al (2014aGuchetl et al ( , 2014b, 17 alleles (2 to 4 alleles per locus) were detected for the same SSR loci, except Ocum-160, with our study. The results of band sizes and allele numbers of SSRs in various studies conducted with different O. cumana populations in the literature and in this study are consistent with each other.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…Pineda-Martos et al (2013) detected 19 alleles (2 to 3 alleles/locus) for the same SSR loci as in our study. In the work of Guchetl et al (2014aGuchetl et al ( , 2014b, 17 alleles (2 to 4 alleles per locus) were detected for the same SSR loci, except Ocum-160, with our study. The results of band sizes and allele numbers of SSRs in various studies conducted with different O. cumana populations in the literature and in this study are consistent with each other.…”
Section: Discussionsupporting
confidence: 79%
“…It has been reported that the analyzed SSR loci have a significant level of heterozygote deficiency, and the main reasons for this are a higher fixation index and selfing rate value. Guchetl et al (2014aGuchetl et al ( , 2014b indicated higher heterozygosity in populations from Russia and Kazakhstan than populations from Romania. It is emphasized that geographic distance, different soil types, and climatic conditions might affect the level of heterozygosity in these populations.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…This was observed in regions with long history of broomrape occurrence [14]. Differences in intra-population genetic diversity were reported in the case of broomrape populations from Russia and Kazakhstan which were more diverse than the Romanian populations [15]. Contrary to that, broomrape introduction into new regions resulted in low genetic diversity and a probable connection to strong founder effect [16].…”
Section: Current Racial Status Of Broomrape World-widementioning
confidence: 92%
“…However, this is currently hampered by the limited availability of genetic tools in O. cumana , since most of the research has been carried out on the crop host, the sunflower. The few genetic studies in O. cumana have mainly focused on population structure and genetic diversity analyses (Castejón-Muñoz et al, 1991; Gagne et al, 1998; Pineda-Martos et al, 2013, 2014; Guchetl et al, 2014; Molinero-Ruiz et al, 2014; Martín-Sanz et al, 2016). These studies concluded that the populations parasitizing sunflowers were characterized by low intra-population diversity and, in general, low differentiation between populations.…”
Section: Introductionmentioning
confidence: 99%